How to improve governance a new framework for analysis and action - De Ferranti, David M. (Washington, D.C. Brookings Institution Press, 2009)
"Emphasizes the need for a comprehensive analytical framework that considers transparency, accountability, governance, and corruption throughout the calculus. Discusses how it can be applied to different countries to help analyze the current situation and identify potential areas for improvement, assessing their relative feasibility and the steps needed to promote them"--Provided by publisher.
Part I: The challenge -- Introduction -- Do transparency, accountability, governance, and corruption matter? -- Part II: The response -- Overview -- Principals and agents -- Interest group dynamics -- Signals and actions -- Political systems -- Interventions -- Part III: Operationalizing the framework -- Application at country level -- Appendixes: Country case studies -- A. Transparency and accountability in Ghana?s budget process / Vitus Azeem -- B. Transparency and accountability in Kenya?s budget process / Gilbert Khadiagala -- C. Transparency and accountability in Peru?s budget process / Cecilia Zavallos -- D. Transparency and accountability in Mexico?s budget process / Juan Pardinas -- E. Transparency and accountability in Thailand?s budget process / Bjoern Dressel -- F. Four composite country cases of attempted governance reform.
Keywords: Government accountability; Transparency in government; Political corruption -- Prevention; Government accountability -- Case studies; Transparency in government -- Case studies; Political corruption -- Prevention -- Case studies